2018
DOI: 10.1111/jgs.15503
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and Delirium in Older Adults: A Systematic Review and Meta‐Analysis of the Literature

Abstract: OBJECTIVES To evaluate the relationship between frailty and delirium. DESIGN Systematic review and meta‐analysis. SETTING MEDLINE, EMBASE, PubMed, Scopus, Web of Science, and Google Scholar databases were searched for articles on frailty and delirium published on or before October 31, 2017. PARTICIPANTS Individuals aged 65 and older. MEASUREMENTS Two authors independently reviewed all English‐language citations, extracted relevant data, and assessed studies for potential bias. Articles involving pediatric or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
109
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(127 citation statements)
references
References 43 publications
(236 reference statements)
5
109
0
7
Order By: Relevance
“…While the literature proposes a myriad of risk factors for the development of POD, differences in the methodology based on different definitions of delirium, differences in assessment of both risk factors and delirium and others, do not allow for a definitive list of risk factors. In conclusion, confounding by potential risk factors not addressed within this study (eg, frailty or cognitive impairment) may limit the application of the results found within this study 10 11…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…While the literature proposes a myriad of risk factors for the development of POD, differences in the methodology based on different definitions of delirium, differences in assessment of both risk factors and delirium and others, do not allow for a definitive list of risk factors. In conclusion, confounding by potential risk factors not addressed within this study (eg, frailty or cognitive impairment) may limit the application of the results found within this study 10 11…”
Section: Discussionmentioning
confidence: 84%
“…The consequences of a POD are very different and range from prolonged hospital stay, increased risk of wound infections, reduced quality of life, more frequent discharge into nursing homes to increased mortality in the first year after surgery 6–9. Recent literature suggests a significant association between frailty and the development of POD with an OR of almost 10, while limitations are considerable due to notable methodological heterogeneity between the methods of studies on such associations 10. Another risk factor for the development of POD may be a preoperative cognitive impairment, as observed in patients undergoing vascular surgery with a demonstrated OR of greater than 2 11…”
Section: Introductionmentioning
confidence: 99%
“…Since frailty is a factor that compromises the ability to cope with internal and external stressful elements, it is easy to understand why from 2010 frailty has also been related to delirium [109][110][111], and has been confirmed as a predisposing factor for delirium in a meta-analysis by Persico et al [112], although the paucity of studies.…”
Section: Delirium Prevention By Targeting Frailty With Physical Exercisementioning
confidence: 99%
“…curing delirium is relatively simple with an early diagnosis, however, a late diagnosis will result in adverse outcomes, including functional decline, increased risk of dementia, falls, pressure sores, and even death (Moon & Park, 2018;Persico et al, 2018;Reynish et al, 2017).…”
mentioning
confidence: 99%